2020
DOI: 10.1111/1346-8138.15246
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐related adverse events correlate with improved survival in patients with advanced mucosal melanoma treated with nivolumab: A single‐center retrospective study in Japan

Abstract: Immune‐related adverse events (irAE) were reported to be associated with better outcomes in various cancers treated with the immune checkpoint inhibitor nivolumab. Considering that their development depends on host immune activation, irAE may reflect antitumor response in mucosal melanoma (MM). This single‐center retrospective study including patients with advanced MM receiving nivolumab monotherapy between August 2014 and September 2018 investigated whether the development of irAE was associated with clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
0
17
1
Order By: Relevance
“…The onset of irAEs has also been associated with improvements in PFS and OS in other carcinomas (25). However, the onset of irAE may not be a predictor of effectiveness because there is no clear relationship between the onset of irAE and the onset of response in other carcinomas (26,27). In the present study, the timing of onset of irAE was also varied and not clearly associated with the timing of onset of response (Figure 1).…”
Section: Discussioncontrasting
confidence: 50%
“…The onset of irAEs has also been associated with improvements in PFS and OS in other carcinomas (25). However, the onset of irAE may not be a predictor of effectiveness because there is no clear relationship between the onset of irAE and the onset of response in other carcinomas (26,27). In the present study, the timing of onset of irAE was also varied and not clearly associated with the timing of onset of response (Figure 1).…”
Section: Discussioncontrasting
confidence: 50%
“…Nivolumab was independently assessed in 12 studies. 17,2939 A post-marketing surveillance study is ongoing to evaluate nivolumab (2 mg/kg every 3 weeks) for Japanese patients with melanoma from approximately 100 institutions since the nivolumab approval date (4 July 2014). 30 In the interim analysis, the estimated median OS was 379 days in the overall population, and 340 days for MM.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, seven independent single-center, retrospective studies showed that MM patients treated with nivolumab had an ORR from 9.5% to 50.0% and a median PFS from 2.1 to 10.2 months. 29,[34][35][36][37][38][39] Pembrolizumab was independently assessed in four studies. 26,[40][41][42] 41 Fifteen patients received 2 mg/kg pembrolizumab every 3 weeks for up to 35 cycles (approximately 2 years).…”
Section: Anti-ctla-4 Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Freeman-Keller reported an epidemiological correlation between the efficacy of nivolumab and irAEs caused by this agent [95]. Several retrospective studies and case reports have also supported this hypothesis [95][96][97][98]. Taken together, these reports suggested correlations between the efficacy of anti-PD1 Abs and several irAEs, and that CD163 + TAMs play a key role in inducing the efficacy of anti-PD1 Abs as well as several irAEs.…”
Section: Roles Of Tams In Immune-related Adverse Events Iraesmentioning
confidence: 84%